ANALYSIS OF THE IMPLEMENTATION OF EXPERIENTIAL LEARNING, COACHING, AND IN-CLASS TRAINING AS A TALENT DEVELOPMENT PROGRAM: CASE STUDY AT PT KERETA API INDONESIA (PERSERO) - Puspitowati, Ririn
This study examines the effectiveness of a Talent Development Program at PT Kereta Api Indonesia (PT KAI). The program integrates experiential learning, coaching, and in-class training within the 70:20:10 framework to enhance talent's skills and performance. High-potential employees, referred to as "Talents," participated in a comprehensive development program based on the 70:20:10 framework, which included experiential learning, coaching, and in-class training. Using a mixed method approach, this study first utilized a quantitative approach, revealing a significant difference in performance and competency after one year. Participants conducted an assessment process before the program started to assess their competency and performance scores. To perform a more thorough examination of the implementation of the program, research was also conducted using semi-structured interviews with Talents in senior and middle management positions, as well as program management. Quantitative analysis revealed that Talents showed significant enhancements in both their competency and performance after one year of participating in the program. Nevertheless, a thorough analysis of the results unveiled an unexpected trend: while competency improved for Talent in middle- and low-level managerial positions, a concerning decline was noted among those occupying senior management positions. The qualitative analysis revealed a lack of standardization, particularly in experiential learning and coaching for senior management talent, leading to less-than-optimal results. The study proposes that integrating experiential learning, coaching, and in-class training into the 70:20:10 framework shows potential for improving Talent's competence and performance, as long as issues related to standardization are properly addressed. Although there were significant enhancements in general competency and performance, slight inconsistencies at various levels of management underscore the crucial requirement for standardization.